Public Perception and Willingness Towards Bystander Cardiopulmonary Resuscitation (CPR) Training and Performance in Pakistan - Khan, Uzair Ali; Khan, Ayaan Ali; Khan, Zoya Ali; Hinna, Rashk e; Khattak, Muhammad Bilal; Khan, Rao Saad Ali (Scripta Medica, 2023)
Background/Aim: Bystander cardiopulmonary resuscitation (CPR) during out-of-hospital cardiac arrest increases both survival rates and neurological recovery, but in Pakistan, an alarmingly low 2.3 % of these individuals receive bystander CPR. This study was designed to identify the reasons that affect the perception and willingness of the public toward bystander CPR training and performance in Lahore, Pakistan. Methods: A CPR master trainer from the USA visited various organisations from 1 December 2022 to 31 January 2023, to conduct training sessions. Before and after the training, a questionnaire was distributed among respondents to fill in. The subjects were asked to answer questions about their perception and willingness to perform bystander CPR. Results: Out of 401 participants, 240 completed the survey, with a response rate of 59.85 %. The majority of them were males [146 (60.8 %)], 215 (89.6 %) were below the age of 40, 107 (44.6 %) were graduated, 182 (75.8 %) never participated in any CPR training, mainly due to their ignorance towards the importance of bystander CPR (52.8 %) and 152 (63.3 %) were eager to participate in the CPR training course. Furthermore, the leading problem in providing bystander CPR was lack of technique or fear of possible harm that can be proved fatal (48.8 %), followed by concerns related to involvement in any legal procedure (10.0 %). Conclusions: Bystander CPR is still uncommon in Pakistan. Participants were reluctant to perform bystander CPR because of various concerns and fears. Lack of proper skill and causing additional harm were the main reasons associated with this. Hence, while improving CPR training and public education, these findings must be considered.